A Classificação Internacional de Funcionalidade, Incapacidade e Saúde (CIF) em cenário de prática: explorando a vivência e a autoeficácia de terapeutas ocupacionais da atenção básica - Mariana Pereira Veloso (2023)
The International Classification of Functioning, Disability and Health (ICF), a model recommended by the World Health Organization (WHO) and based on the biopsychosocial perspective, considers that it is from the interaction between the subject with a health condition and his life scenario, which emerge the results of functionality or incapacity. The ICF use in health systems resonates with aspects of teamwork in the context of Primary Care (PC), being proposed as a tool for the operationalization of comprehensiveness and territoriality of health interventions. The Expanded Family Health Center and Primary Care (NASF-AB, in Portuguese ), one of the interprofessional teams that work in AB, has an occupational therapist in its composition. Occupational Therapy as a profession aims to restore occupational performance considering the interaction of individuals with the context, aligning its assumptions with the assumptions of the ICF. However, there is little use and knowledge of the ICF by occupational therapists, although it is undeniable that PC has a fertile environment for the application of the ICF, which can favor the planning of actions. However, information or knowledge alone is no guarantee that its use will be implemented. For the learning and expression of specific competences, it is necessary that people have confidence that they will be able to successfully perform a task to achieve their goals. The belief that the individual has about his ability to successfully perform a certain activity is called self-efficacy and can affect the individual's choices and performance. In addition, issues related to the profession, the interaction between team members and the management of services permeate the perception of occupational therapists regarding the possibility of implementing the ICF in PC. In this sense, the objectives of this work were: 1) to reveal the vision of occupational therapists about the use of the ICF in Primary Care; 2) verify the knowledge of AB occupational therapists about the ICF; 3) to document self-efficacy for using the ICF and factors associated with it among occupational therapists working in AB in Belo Horizonte. An exploratory observational study was carried out using mixed methods, in two stages. In the first, the self-efficacy, general and for the use of the ICF, and the level of knowledge about the ICF of PBH occupational therapists was verified, using the backward linear regression model. In the second stage, a focus group was held with occupational therapists, with content analysis. 38 occupational therapists participated in the study, and 6 of these 38 professionals participated in the focus group. There is a lack of knowledge (average 4.76), especially with regard to codes and qualifiers, and low self-efficacy (average 2.79) for using the ICF. The use of ICF in work processes and general self-efficacy were identified as explanatory variables for the variance of self-efficacy for ICF, with an adjusted R² of 0.48. From the analyzed narratives, three categories emerged about the vision of occupational therapists regarding the use of the ICF in the practice setting: Vision of the ICF and the formation and clinical practice of Occupational Therapy; ICF vision and teamwork; and Vision of the CIF, the SUS and the panorama of service management. There is little knowledge about the ICF constructs and domains by occupational therapists, and practical training should be offered to implement it. The knowledge of occupational therapists about the biopsychosocial model can help in their own training and in the training of other team members and be useful in the implementation of the ICF in the network services, although it needs a better structure and management strategies to favor its execution.